Da cozinha ou da sala? "Que horas ela volta?" Estudo de recepção com domésticas e patroas - Nunes, Everton de Almeida (2018)
The present research is a reception study conducted with domestic and female employers that used as a mediation product the Brazilian feature film "The Second Mother" Screenplay and direction of filmmaker Anna Muylaert. The main objective of the work was to highlight the variety of meanings produced by domestic and female bosses about the film product, seeking possible symbolic constructions that cross the sociocultural dimension of domestic work relations. The research was carried out with volunteer women who experienced in some way the dynamics of domestic work, whether as a worker or as a contractor of this type of service. What was observed with the work developed was the emergence of categories of analysis interconnected with socio-historical and socio-cultural aspects of domestic work. The method used in the research was Grounded Theory, therefore, we used the methodological assumptions developed by Strauss and Corbin (1997), in addition to the analyzes developed by Charmaz (2006) and Ferreira (2011). The steps covered included the description of the film, highlighting the semantic direction and the evidence of the key moments of the work. Subsequently, with the presentation of the film to the groups of housewives and mistresses, we developed a focal dynamics and proceeded to the subsequent stages of analysis of the data advocated by the Grounded Theory. In the last stage of the research process, we evaluated the results found in the light of the deductive studies, to which we were able to verify relevant considerations about the culture of the domestic work through the cinema.